Alternative development financing mechanisms: Pre-crisis trends and post-crisis outlook - Sam Jones (Danish Institute for International Studies (DIIS), 2009)
Over the past decade, development policy has witnessed a clear shift towards a poverty reduction agenda. Unsurprisingly, this has been accompanied by changes in views concerning development finance. A dominant refrain of the present agenda is that 'traditional' approaches to development finance, characterised by official bilateral and multilateral assistance to discrete projects through a combination of loans and credits, have been inadequate. In response, reforms of traditional aid and alternative approaches to financing are being advocated. This study assesses the recent evolution of non-traditional approaches to development finance. It includes 1) an examination of the characteristics of the alternative financing mechanisms that have emerged over recent years; 2) an analysis of their (combined) contribution to addressing development financing challenges in the poorest countries; and 3) considerations over the future prospects of alternative financing mechanisms. Previous studies retain a relatively narrow focus and therefore fail to capture either the comparative characteristics of alternative financing mechanisms or the extent to which different instruments (or actors) may act as substitutes or complements to development assistance. This study seeks to address these shortcomings by providing an integrated and up-to-date perspective on recent developments, focussing on the extent to which more specific financing challenges are addressed. The study concentrates mainly on issues relevant to sub-Saharan Africa as getting development finance right” seem to be most important here.
Keywords: 300; Entwicklungshilfe; Entwicklungsfinanzierung; Millennium Development Goals; Internationaler Finanzmarkt; Finanzmarktkrise; Niedriglohnländer